2018
DOI: 10.1103/physrevd.98.021902
|View full text |Cite
|
Sign up to set email alerts
|

Strings on NS-NS backgrounds as integrable deformations

Abstract: We consider the world-sheet S matrix of superstrings on an AdS 3 × S 3 × T 4 NS-NS background in uniform light-cone gauge. We argue that scattering is given by a CDD factor that is nontrivial only between opposite-chirality particles, yielding a spin-chain-like Bethe ansatz. Our proposal reproduces the spectrum of nonprotected states computed from the Wess-Zumino-Witten description and the perturbative tree-level S matrix. This suggests that the model is an integrable deformation of a free theory similar to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
188
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(189 citation statements)
references
References 71 publications
(139 reference statements)
1
188
0
Order By: Relevance
“…This wealth of parameters will allow for a precision-spectroscopy comparison of new proposals for computing the spectrum of strings on AdS 3 backgrounds, see e.g. [45,46]. This paper is organised as follows.…”
Section: Jhep08(2018)097mentioning
confidence: 99%
“…This wealth of parameters will allow for a precision-spectroscopy comparison of new proposals for computing the spectrum of strings on AdS 3 backgrounds, see e.g. [45,46]. This paper is organised as follows.…”
Section: Jhep08(2018)097mentioning
confidence: 99%
“…These D = 2 models turn out to be structurally very similar to the Bagger-Galperin action describing a D = 4 N = 1 Born-Infeld theory, which possesses extra non-linearly 12 The careful reader may find that the flow can also be satisfied by other supercurrent-squared operators, J 2 − rX X , with arbitrary r because of the linearity between J 2 andX X . It is worth pointing out the same thing happens in D = 2 [21].…”
Section: Discussionmentioning
confidence: 81%
“…This is a beautiful connection between TT deformations and a field theory which classically possesses a non-linearly realized D = 3 Lorentz symmetry; for other connections between TT and classical string theory, see, for example, [8][9][10][11][12][13][14][15].…”
mentioning
confidence: 99%
“…Meanwhile, there are other different perspectives on the TT deformation [29,30], and applications in string theory [31][32][33][34][35][36][37][38][39][40][41][42]. More interestingly, from holographic dual point of view, it is suggested that the TT deformed 2D CFT dual to AdS 3 gravity with finite cutoff in the radial direction [43].…”
Section: Introductionmentioning
confidence: 99%